2019
DOI: 10.3389/fpsyg.2019.02231
|View full text |Cite
|
Sign up to set email alerts
|

Family Leisure, Self-Management, and Satisfaction in Spanish Youth

Abstract: Youth values leisure as a right, a source of growth and integral development, and a context for experimentation. It has been shown that organized leisure leads to more benefits than unorganized leisure; when undertaken (Throughout the document, an attempt will be made to use inclusive language, although “under Law 3/2007 of 22 March, for the effective equality of women and men, any reference to positions, persons or groups included in this document in masculine, are to be understood as including both women and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
0
8
0
7
Order By: Relevance
“…It could also mean that the activities they do during their leisure time are not those that they necessarily like or enjoy, but are those they can do. The choice of activity has been shown to be key to the maintenance of physical activity during adolescence [13,17,31].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It could also mean that the activities they do during their leisure time are not those that they necessarily like or enjoy, but are those they can do. The choice of activity has been shown to be key to the maintenance of physical activity during adolescence [13,17,31].…”
Section: Discussionmentioning
confidence: 99%
“…Leisure time, along with the school, has been identified as a perfect moment to practice physical activity and support healthy behaviors, through active play and sports [10,11]. In addition, it is an opportunity for children to choose the activities they engage in (whether active or not) [12][13][14]. Previous studies focusing on leisure time have concluded that physical activity and its practice are affected by individual (age and fitness), psychological (preferences and satisfaction), sociocultural (gender, family and friends) and infrastructural influences (equipment, security and proximity) [13,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations